2020
DOI: 10.32615/ps.2019.107
|View full text |Cite
|
Sign up to set email alerts
|

Special issue in honour of Prof. Reto J. Strasser - Development and aging of photosynthetic apparatus of Vitis vinifera L. during growing season

Abstract: The aim of this study was to examine the development and aging of chosen grapevine leaves in situ during the growing season (130 d) using chlorophyll (Chl) a fluorescence measurements and determining the changes in pigment contents. During the course of photosystems development, the increase of Chl and decrease of anthocyanin contents in leaves was observed simultaneously. On 28 th day, the maximum content of Chl and minimum content of anthocyanins was measured. However, the maximal photosynthetic performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…On the contrary, leaves that are fallen off contain smaller amounts of at least some flavonol species than green leaves in B. pendula (Paaso et al 2017). In anthocyanin producing species, amounts of flavonols may either decrease (Sitko et al 2019), increase or stay constant (Mattila et al 2018) during senescence. Flavonol amount has been shown to increase in response to UV radiation in B. pendula (Morales et al 2010) and in response to coldness in B. nana (dwarf birch; Stark et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, leaves that are fallen off contain smaller amounts of at least some flavonol species than green leaves in B. pendula (Paaso et al 2017). In anthocyanin producing species, amounts of flavonols may either decrease (Sitko et al 2019), increase or stay constant (Mattila et al 2018) during senescence. Flavonol amount has been shown to increase in response to UV radiation in B. pendula (Morales et al 2010) and in response to coldness in B. nana (dwarf birch; Stark et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Chlorophyll fluorescence analysis has become one of the most powerful and widely used techniques available to plant physiologists [26]. Many fluorescence applications detecting and analyzing stress effects on plants are nondestructive and sensitive [27]. Chlorophyll fluorescence shows the state of photosystem II and reflects the extent to which PS II uses the energy absorbed by chlorophyll.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at points K, J, and I corresponded to induction times of approximately 0.3 ms, 2 ms, and 30 ms, respectively. The obvious increase in ΔK indicates damage to the activity of the oxygen-evolving complex (OEC), while a clear appearance in ΔJ is related to the blockage of electron transfer from Q A to Q B [ 25 , 26 ]. On the first day and the 10 th day after the leaves fully unfolded, the ΔV K of the SL groups was lower than the ΔV K_ref but it higher than the ΔV K_ref from the 20 th day onward ( Fig 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al [ 30 ] reported that the chlorophyll content of new leaves gradually increased with the development of leaves, and the net photosynthetic rate (Pn) increased at the same time. Sitko et al [ 26 ] found that the maximum photosynthetic rate of young grape leaves occurred one week after their chlorophyll content peaked. In the present study, the maximum chlorophyll content occurred on the 10 th day after the leaves fully unfolded, and the ABS/CS ratio also concurrently peaked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation